EFEKTIFITAS MODEL PROJECT BASED LEARNING (PJBL) DALAM MENINGKATKAN KREATIVITAS MENGGAMBAR BATIK POLA GEOMETRI TEMA KEBUDAYAAN LOKAL KUDUS - Mahya, Asna; Nur Fajrie; Fitriyah Amaliyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Creativity plays an important role in learning art drawing. Creativity is used to encourage students to be able to develop ideas, imagination, and concepts freely to produce original, varied, and meaningful works. This study aims to determine the effectiveness of the project based learning (PjBL) learning model in increasing students' creativity in drawing geometric pattern batik with the theme of Kudus local culture. This study uses a quantitative method of the Pre-Experimental model with a One-Group Pretest-Posttest design. Data collection through a questionnaire instrument totaling 25 questions. Data analysis uses SPSS 25 with the Shapiro-Wilk technique normality test as a prerequisite test and hypothesis testing with the Paired Sample T-Test and N-Gain tests. The results of the study show that there is an average difference between the pretest and posttest, the average pretest value is 66.36, while the average posttest value is 86.05 and the results of the Paired Sample T-Test with a significance value of 0.000 less than 0.05. Based on the N-Gain test, the average creativity ability was 0.5622, which indicates a moderate category, and the N-Gain percent value reached an average of 56.2194, which is interpreted as quite effective. Therefore, it can be concluded that the Project Based Learning (PJBL) model can improve the creativity in drawing skills of grade IV of SD 3 Klaling.